Representasi Nasionalisme dan Implementasi Profil Pelajar Pancasila pada Film “Susi Susanti - Love All” dalam Perspektif Semiotika Roland Barthes - Rika Ayu Perdana (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2022)
Film is a means of communication in which elements of language are created. It is on this basis that this study seeks to examine the semiotic aspects of the representation of nationalism and the implementation of the Pancasila Student Profile in the film entitled